Blockage of C-X-C Motif Chemokine Receptor 2 (CXCR2) Suppressed Uric Acid (UA)-Induced Cardiac Remodeling - Xu, Mingxi; Zheng, Xu; Wang, Dongxia; Fu, Xiaodan; Xing, Yida; Liu, Yu; Wang, Hongjiang; Kong, Xiaodan (Frontiers in Physiology, 2021)
It has been demonstrated that hyperuricemia induced cardiac dysfunction is via vascular-dependent mechanisms, yet the vascular-dependent mechanisms are not well understood. Uric acid (UA) has been found to stimulate CXCL1 up-regulation in renal tubules from mice subjected to UA-induced nephropathy. Given that CXCL1 is a master chemokine responsible for macrophage recruitment by binding with its receptor CXCR2, we thus hypothesized that UA-induced cardiac injury is via promoting the recruitment of CXCR2+ macrophages into heart, which enhancing cardiac inflammation. Within a mouse model of UA injection (500 mg/kg, twice/day, 14 days), we measured cardiac CXCL1 level. We also tested the efficacy of CXCR2 antagonist on UA-induced cardiac inflammation and remodeling. We found high plasma level of UA induced up-regulation of CXCL1 in heart tissues. CXCR2 antagonist preserved UA-induced cardiac dysfunctions and suppressed cardiac inflammation and fibrosis. Silencing of CXCR2 in human monocytes abolished UA-induced monocyte migration. Thus, the interventions against CXCL1/CXCR2 maybe effective for the prevention and treatment of UA-induced cardiac dysfunction and inflammatory responses.